Symbiosis and ambivalence : Poles and Jews in a small Galician town - Lehmann, Rosa (Berghahn Books, 2001)
Linking the past and present of Polish-Jewish relations, and combining anthropological fieldwork with archival material and secondary literature, this study reveals a pattern of Polish-Jewish interdependence.